Reduced frontal activation with increasing 2nd language proficiency - Stein, Maria; Federspiel, Andrea; Koenig, Thomas; Wirth, Miranka; Lehmann, Christoph; Wiest, Roland; Strik, Werner; Brandeis, Daniel; Dierks, Thomas (Neuropsychologia, 2009)
The factors influencing the degree of separation or overlap in the neuronal networks responsible for the processing of first and second language are still subject to investigation. This longitudinal study investigates how increasing second language proficiency influences activation differences during lexico-semantic processing of first and second language. Native English speaking exchange students learning German were examined with functional magnetic resonance imaging while reading words in three different languages at two points in time: at the beginning of their stay (day1) and 5 months later (day2), when second language proficiency had significantly increased. On day1, second language words evoked more frontal activation than words from the mother tongue. These differences were diminished on day2. We therefore conclude that with increasing second language proficiency, lexico-semantic processing of second language words needs less frontal control. Our results demonstrate that lexico-semantic processing of first and second language converges onto similar networks as second language proficiency increases.